The Correlation between Self Regulated and Self Concept in Learning on Student’s Reading Achievement - Febri Wulandari (Language-Edu, 2019)
This study is intended to find out whether self-regulate and self-concept in learning correlate with student’s reading achievement. The researcher used 57 students of MTs. Khairuddin Gondanglegi, Malang as the subject. The instrument of this research used questionnaire of self-regulate and self-concept in learning and reading test. The design of this research is quantitative research. The researcher used correlation research with multiple regression analysis to analyze this data. The finding of the research is self-regulate and self-concept in learning has no significant correlation on student’s reading achievement. The recommendation for further researchers is the result of this research can be used by the further researchers as a consideration to conduct further research in different aspects such as English skill, research areas, and also research design.